PERANCANGAN PEMBANGKIT LISTRIK TENAGA SURYA ATAP DI HOTEL MEGA DANA - Christ Ave Duga Purba; Ongky Wahyu Wicaksono; I Wayan Arta Wijaya; I Nyoman Budiastra (Program Studi Teknik Elektro UNUD, 2023)
The utilization of renewable energy is one of the solutions to overcome the increasing electricity demand. One of these solutions is to install Solar Power systems on the roofs of offices, industries, or households. This study targets to meet electricity demand by utilizing the roof of the Mega Dana Hotel as a place for the installation of solar panels, the solar panel will later produce electrical energy to meet the electricity needs of the hotel bars. The simulation results of the production of electric energy at Hotel Mega Dana's solar panel system using an application called Helioscope. This study analyzes the economics of designing a rooftop solar power system at Hotel Mega Dana. The feasibility of this research investment is assessed from the value of NPV, PI, and DPP. According to the data obtained, the Hotel Mega Dana building has a roof area of 655.92 m 2. The study used 39 solar panel modules, 1 20kW inverter, and 5 48V 100 Ah TLO batteries, the system can produce 17,6 kWp of power, with a total annual energy production of 21.83 MWh to supply electricity for the bar at Hotel Mega Dana. This research was planned with an initial capital of IDR 254,578,500, a PI value of 1.09, and a DPP value of 21.9 years. The results of this research analysis can be considered feasible because the design has a positive NPV value and is expected to return investment at 21.9 years out of 25-years project life.